Pengembangan Digitalisasi Umkm Masyarakat Kelurahan Tambak Wedi Kecamatan Kenjeran Kota Surabaya - Bella Safitri Sandi; Sri Muljaningsih; Mohammad Wahed (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The Industrial Revolution 4.0 has a very positive impact on the development of technology and information. Modernization and technological advances have developed a lot in various sectors, one of which is Micro, Small and Medium Enterprises (MSMEs) which also take advantage of moving through various innovations to stay afloat along with the rapid changes of the times. The use and utilization of technology is also one of the efforts of MSMEs in Tambak Wedi Village to increase the number of consumers through digital-based marketing. Through KKN activities in the Tambak Wedi Village community, Kenjeran District, Surabaya City as a form of student service to the community to provide assistance to MSME actors in optimizing digital-based product marketing. The method used in this activity is a qualitative approach through socialization, implementation and mentoring. The results of this activity are product content creation, logo rebranding and social media management that can be used by MSMEs in marketing their products on social media. This activity affected the local population, people began to sell in the digital market and in a gradual way became financially independent